A Review of Design Methods of Transverse Reinforcement of Concrete Bridge Deck on Prestressed Girders - Najiyu, Abubakar; Redzuan, Abdullah; Ahmad Kueh, Beng Hong; Mohammad Salleh, Yassin (IOP Publishing Ltd., 2019)
A review of current practices in designing the transverse reinforcement of concrete bridge slab supported by wideflange prestressed-T girders is presented. Slabs are commonly assumed to be supported continuously at the center points of girders, neglecting the effect of the girder flange stiffness. The design in this manner may produce conservative transverse reinforcement of the slab. As alternative a newly constructed bridge deck is chosen as a case study where the design based on this conservative assumption is compared with that considering the girder flange length, thickness and rigidity. The results of these two designs are compared. It is found that the amount of transverse reinforcement of the concrete slab obtained from the conventional design is considerably larger than that considering the girder flange stiffness. This promising finding warrants further investigation of the latter approach focusing on the effect of girder flanges in taking bridge loading in the transverse direction.